DISTRIBUTION OF DIFFERENT BLOOD GROUPS DATA FROM BLOOD BANK REGISTRY IN PESHAWAR, PAKISTAN - Idrees, Muhammad; Khan, Muhammad Ihtesham; Malik, Saira Nasr (Journal of Postgraduate Medical Institute, 2022)
Objective: To determine the distribution of ABO and Rh-blood groups in district Peshawar. Methodology: This was a Cross-sectional descriptive study, done in the Blood Bank of Khyber Teaching Hospital Peshawar. Participants of all ages and gender referred to the Blood bank for blood grouping and blood donors were included. Sampling was done using the non-probability purposive sampling method. Blood grouping was done using commercially available Antisera by the trained Blood Bank clinical technician. The blood groups were recorded in the proforma and data was analyzed. Standard deviation and Mean were used for quantitative data. Qualitative data was analyzed using Frequency and percentages. Results: Mean age of 2902 recipients was 39 ± 9.2 (range 18-60) years. There were 2900 (99.9%) males and 2 females (0.1%), because females are mostly deferred due to not fulfilling donor selection criteria. The commonest blood group was B (30.9% cases), followed by blood group A (29.8% cases), O (28.3%), and AB (10.8%). Rhesus positive blood group was common (92.1%) as compared to Rhesus negative (7.9%). Conclusions: Blood group B-positive was the commonest blood group. AB-negative was the rarest one.